Washing the Dead, Weaving the Invisible: Magical Realism in Sinan Antoon’s The Corpse Washer - Abdul Salaam Hummadi Al-Moosawi (مجلة الباحث, 2025)
The current study examines how Sinan Antoon adeptly employs magical realism in The Corpse Washer (2010) to delineate the psychological and cultural toll perpetrated by decades of violence in Iraq. The paper examines Jawad’s experiences as a reluctant corpse washer and aspiring artist, recurring nightmares, Shiite funerary rituals, and symbolic landscapes, aiming to show how Antoon adroitly use magical realism to critique the demolition of Iraqi identity during the American occupation and resist Western-centric accounts of the 2003 War. Through a qualitative literary analysis grounded in magical realism theory and postcolonial frameworks, the study explores the novel’s blending of the mundane and surreal to voice Iraq's collective trauma and cultural resilience. The main findings reveal that rituals such as corpse washing and symbols like the death-fed pomegranate tree serve as subversive articulation to the hegemonic discourses, reclaiming agency of Iraqis whose country is engulfed by narratives of loss. Thus, the employment of magical realism in the novel not only uncovers the fragmentation of Iraqi identity but also espouses that the Iraqi cultural heritage persists amid devastation. This paper contributes to postcolonial literary scholarship by bringing to the fore Iraqi narrative of global war literature and highlights the importance of magical realism as an implement for marginalized nations to subvert erasure. The paper concludes with suggestions for further studies on gender roles and resilience in postcolonial contexts